2004
DOI: 10.1590/s0100-879x2004000900011
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide in the treatment of focal segmental glomerulosclerosis

Abstract: Prednisone is the initial treatment of primary focal segmental glomerulosclerosis. However, when immunosuppressive agents in combination with steroids are used in the treatment of prednisone-dependent and prednisone-resistant patients the remission rate is variable. We report a long-term trial using cyclophosphamide (2.0 to 3.0 mg/kg body weight for 12 weeks) in combination with prednisone (1.0 to 2.0 mg/kg body weight), as compared with prednisone alone for the treatment of prednisone-resistant and frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…14 Complete remission among 33.3% children was noted by Brazilian researchers using a combination of steroid and cyclophosphamide. 19 It was also noted in the present study that 53.3% of the cases using this combination therapy reported relapse within two years of stopping this protocol and they were started on cyclosporine and achieved sustained remission. Previous local data also found 36% of the patients using cyclophosphamide and steroid to report relapse later and were shifted to cyclosporine who achieved sustained remission.…”
Section: Discussionsupporting
confidence: 72%
“…14 Complete remission among 33.3% children was noted by Brazilian researchers using a combination of steroid and cyclophosphamide. 19 It was also noted in the present study that 53.3% of the cases using this combination therapy reported relapse within two years of stopping this protocol and they were started on cyclosporine and achieved sustained remission. Previous local data also found 36% of the patients using cyclophosphamide and steroid to report relapse later and were shifted to cyclosporine who achieved sustained remission.…”
Section: Discussionsupporting
confidence: 72%
“…In the two trials comparing cyclophosphamide with prednisone [27, 28], 35% of 34 children achieved remission with prednisone alone. Similarly, a large observational study [29] found that 27% of children treated with oral cyclophosphamide achieved remission but that this rate did not differ from children given prednisone alone.…”
mentioning
confidence: 94%
“…Prolonged corticosteroid for 6-12 months may have a remission rate of 28% with increased rate of iatrogenic complications [5]. A partial or complete remission was reported with oral cyclospsphamide with a remission rate close to continued steroid therapy alone [31]. One trial compared oral cyclophosphamide with IV cyclophosphamide and reported no significant difference [32].…”
Section: Discussionmentioning
confidence: 99%